Resistance as Existentialism in Camus' The Guest - Pratiwi, Jero Ayu Manik; Udayana, I Nyoman; Ayu Widiastuti, Ni Made (Humanis, 2025)
Albert Camus’ The Guest serves as a profound illustration of personal resistance against colonialism. This study explores resistance as an existentialist concept in Albert Camus’ The Guest, analyzing how individual autonomy and moral dilemmas reflect Jean-Paul Sartre’s existentialist philosophy. This research aims to demonstrate how resistance in the narrative is not merely political but also philosophical, embodied in the characters’ struggles with freedom and responsibility. Using Sartre’s existentialism as the theoretical framework, this study employs a qualitative research method, analyzing textual elements through close reading and interpretation. The findings reveal that the act of resistance in The Guest manifests through Daru’s micro expression, reflecting Sartre’s notion of existence precedes essence, condemned to freedom and responsibility, anguish, and forlornness. Ultimately, the study highlights how existential resistance challenges not only against external forces but also the burden of their own freedom.